Intention towards the Early Detection of Cervical Cancer Uptake among University Students - Erika Nurramadhani; Ditiya Novani; Febi Nur Amelia; Hoirun Nisa (Al-Sihah : The Public Health Science Journal, 2022)
The intention to take the Visual Inspection of Acetatic Acid (VIA) test, an early detection method for cervical cancer, in Indonesia is considerably still low due to the lack of both awareness and intention of cancer screening using the VIA test. In fact, the VIA test is a goverment‘s program aimed to prevent and to suppress the increasing number of cervical cancer. The purpose of this study was to determine the factors associated with the intention to take the VIA test among university students. This study applied a cross-sectional design with a sample size of 314 respondents. The respondents in this study were university students selected using a volunteery sampling technique. The data were collected by an online questionnaire (i.e., Google Form). Multivariate analysis used a logistic regression test. The proportion of respondents who had the intention to utilize the VIA test was 74.5%. The results of the multivariate analysis depicted that the intention to take the VIA test was associated with the health field of study (p-value: <0.001; OR=3.09; 95%CI=1.72－5.54) and positive attitude towards early detection of cervical cancer (p-value: <0.001; OR=2.73; 95%CI=1.55－4.79). The intention to take the VIA test was associated with the field of health studies, positive subjective norms, positive attitudes, and perceptions of positive behavioral control. Therefore, there should be a necessity for education, especially for non-health students onto the importance of taking the VIA test by utilizing educational facilities at their home universities.